On the radii of convexity and starlikeness for some special classes of analytic functions in a disk - Kotsur, I. M.; Kotsur, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We introduce the class O α, 0≤α≤1, of functions w=ƒ(z), ƒ(0)=0, ƒ′(0)=0,..., ƒ (0) (n−1) =0, f (n)(0)=(n-l)! analytic in the disk |z|